Computational Methods For Water Quality Index Calculation Using Real-Time Measurement System - Koleva, Radmila; Zaev, Emil; Babunski, Darko; Stefanovski, Damjan; Rath, Gerhard (IEEE, 2024)
The main focus point of this research is the analysis of the computational methods used for Water Quality Index (WQI) calculation using a real-time measurement System. For the calculations, a prototype of a cheap IoT system for measuring surface water quality has been used. The monitoring system incorporates sensors for temperature, turbidity (NTU), and pH. These parameters are measured through probes submerged directly into the water sample. The probes are connected to an Arduino Uno microcontroller, and through Bluetooth wireless communication, the measured data is transferred to a mobile device and displayed on an application. Also, the measured data are saved on a personal computer for their further processing. The collected data from the IoT system is calculated and presented in real time. Using real-time monitoring we can get instant information for the possible water contamination.
Keywords: real-time monitoring; water quality index; IoT; measurement